(3GdJMdjd GdEFJeGfj (B/s - (3Ndhaj, hgjHI s ((3YeGf(B: s (3OGQ GdEYUGQ GdYdej ddfTQ hGdJhRjY(B, s, 2016)
(3jVe eaghe GdEFJeGf GdeUQaj hfTCJg, GdJMdjd GdEFJeGfj hYedjI efM GdEFJeGf aj GdeUQa, GdbQhV GdeUQajI hELQGAGJ GdJehjd, CgejI GdbQhV GdeUQajI hELQGAGJ efM GdbQhV GdeUQajI,CTcGd GdJehjd hCfhGY GdEFJeGf habG deOI GdJehjd, GdOhQ GdhbGFj dCfXeI GdJCejf Ydi GdhOGFY, GdLhGfH GdTQYjI dHWGbI GdEFJeGf(B.s
(3HHdjhZQGajG(B: (3U(B.218-222 s
Keywords: (3GdEFJeGfs; (3GdEFJeGf GdeUQajs; (3GdEbJUGO GdJMdjdjs